2015
DOI: 10.1177/0037549715595135
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-order urban wind interference

Abstract: A novel approach is demonstrated to approximate the effects of complex urban interference on the wind-induced surface pressure of tall buildings. This is achieved by decomposition of the domain into two components: the obstruction model (OM) of the static large-scale urban context, for which a single computational fluid dynamics (CFD) simulation is run; and the principal model (PM) of the isolated tall building under design, for which repeatable reduced-order model (ROM) predictions can be made. The ROM is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…All of the surveyed papers about wind & ventilation were domain‐specific ones (43). Wilkinson et al present a data generation technique to approximate complex computational fluid dynamics (CFD) using an artificial neural network [WBH14]. The other surveyed papers were primarily analysis contributions that relayed on CFD for building‐level [AKH19] or neighborhood‐level [EGAB17, ZKL*21] wind load analysis (Figure 12 (Super‐imposition)), wind power potential [SDP20], inner building ventilation [SL19,HP20], wind impact on urban climate [GBI14,DL19, HP21], pollution dispersion [GL19,ZWLZ22,HZL*23, LMS*23], or the interplay between sunlight access and wind for thermal comfort [JY20].…”
Section: Primary Dimensions (Why)mentioning
confidence: 99%
“…All of the surveyed papers about wind & ventilation were domain‐specific ones (43). Wilkinson et al present a data generation technique to approximate complex computational fluid dynamics (CFD) using an artificial neural network [WBH14]. The other surveyed papers were primarily analysis contributions that relayed on CFD for building‐level [AKH19] or neighborhood‐level [EGAB17, ZKL*21] wind load analysis (Figure 12 (Super‐imposition)), wind power potential [SDP20], inner building ventilation [SL19,HP20], wind impact on urban climate [GBI14,DL19, HP21], pollution dispersion [GL19,ZWLZ22,HZL*23, LMS*23], or the interplay between sunlight access and wind for thermal comfort [JY20].…”
Section: Primary Dimensions (Why)mentioning
confidence: 99%
“…In addition they performed a correlation analysis between the price and the rated power of vertical axis wind turbines (VAWT) rated below 5000 kWh. Wilkinson et al demonstrated a new approximation approach of computational fluid dynamics in high rise buildings with complex wind interference (Wilkinson et al, 2014). Wang et al compared and analyzed seven different urban tissues using CFD simulations in the area of Beijing.…”
Section: State Of the Artmentioning
confidence: 99%
“…The underlying approach is still in its infancy, the potential breadth of its application is however supported by a wide array of related research, investigating ML for simulation of wind, 19–21 structural 22 and climatic performance, 23 formfinding and analysis of bending active structures, 24 macroscopic material behaviour, 25 driving styles of cars 26 and the utilization of heavy equipment on construction sites. 27…”
Section: State Of the Artmentioning
confidence: 99%